2023
DOI: 10.3390/fishes8020108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Freeze-Thaw Cycles on Protein and Lipid Oxidation, Microstructure and Quality Characteristics of Rainbow Trout (Oncorhynchus mykiss)

Abstract: Multiple freeze-thaw cycles due to temperature fluctuations irreversibly damage the muscle tissue of fish, thereby reducing their edibility. The aim of this study was to determine the effects of the number of freeze-thaw (F–T) cycles on protein and lipid oxidation, microstructure, physical index, and nutritional quality of rainbow trout muscle. The results showed that F–T cycles accelerated protein carbonyl formation and thiobarbituric acid reactive substances (TBARS) generation (p < 0.05), as well as incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…Considering the contraction of myofibrillar lattice spacing caused by ice growth during freezing and thawing, it impacts the optical density, resulting in increased light scattering and a dimmer meat color. This finding has been preliminarily validated in recent research. ,, Generally, meat color relies not only on the pigment contribution but also on the essential muscle structural attributes. Therefore, open-minded consideration is required for understanding color variations in meat during the freezing and thawing processing.…”
Section: Impact Of Ice On the Quality Of Muscle Foodsupporting
confidence: 61%
See 1 more Smart Citation
“…Considering the contraction of myofibrillar lattice spacing caused by ice growth during freezing and thawing, it impacts the optical density, resulting in increased light scattering and a dimmer meat color. This finding has been preliminarily validated in recent research. ,, Generally, meat color relies not only on the pigment contribution but also on the essential muscle structural attributes. Therefore, open-minded consideration is required for understanding color variations in meat during the freezing and thawing processing.…”
Section: Impact Of Ice On the Quality Of Muscle Foodsupporting
confidence: 61%
“…This finding has been preliminarily validated in recent research. 55,58,61 Generally, meat color relies not only on the pigment contribution but also on the essential muscle structural attributes. Therefore, open-minded consideration is required for understanding color variations in meat during the freezing and thawing processing.…”
Section: Quality Deterioration In Muscle Food Duringmentioning
confidence: 99%
“…MDA is an indicator of lipid peroxidation in tissues and oils. High levels of MDA are thought to play a role in oxidative stress and the pathogenicity of atherosclerosis [ 115 ] . TBARS varies significantly (P < 0.05) in raw Cyprinus carpio, Arius parkii, and Ethmalosa fimbriata oil compared to raw Polydactilus quadrifilis oil different species ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aydin and Gokoglu [ 113 ] showed that during freezing at −20 °C and storage at −18 °C in Engraulis encrasicholus oil, TOTOX value increased compared to raw fish oil. The increase in these values during smoking and boiling could be due to the hydrolysis of the ester bonds releasing the fatty acids which oxidise to give primary and secondary oxidation products which alter the quality of the oil [ 115 ] . The increase in these indices of alteration during freezing could be due to the breaking of double bonds by endogenous enzymes [ 25 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Three grams of sample were weighed and homogenized (Ultraturrax ® , Stauten, Germany) with 10 mL of 7.5% TCA solution. Next, the mixture was homogenized at 5000 rpm for 10 min at 4 • C. The supernatant was used for MDA determination according to Du et al [22] MDA-TBA complex was determined at 530 nm using a microplate spectrophotometer (ThermoFisher Scientific Oy, Vantaa, Finland). The results were expressed as µmols MDA per kilogram of muscle.…”
Section: Lipid Oxidation Testmentioning
confidence: 99%